Analysis of the Operational Application of Military Capabilities in Counterinsurgency within a Military Operations Other than War Framework in the Papua Region - Mella, Stellar Nube; Pujo Widodo; Susaningtyas Nefo Handayani Kertopati (CV. AFDIFAL MAJU BERKAH, 2024)
The military plays a key role in Indonesia’s fight against armed separatist -insurgent groups. Not only that is it mandated by law, the military’s involvement in counterinsurgency is also necessitated by practical demands and the nature of the conflict where separatist insurgents would often utilize guerilla warfare attacks such as exploitation of terrain to ambush security force positions. Other than the ability to inflict lethal force, the military also possess “soft” capabilities needed to win hearts & minds and facilitate the implementation of government policies. This study aims to analyze the operational application of military capabilities in counterinsurgency within an MOOTW framework in Papua. This article utilized a qualitative research design with a deductive analysis method where the researcher seeks to deductively analyze the data collected by understanding and studying theories from various literatures related to the research topic and then critically analyzing the data to answer the research questions as it pertains to the utilization Indonesia’s military capabilities as means within an operational plan to implement the counterinsurgency strategy, as well as the challenges in conducting such operations & the relative limitations of the capabilities of the Indonesian military that can be utilized. The results of this study found that the military capabilities are applied in territorial, intelligence, and combat/ enforcement operations. The challenges to the operational application include lack of cultural competence, actionable intelligence, unified command, as well as suitable metrics. In conclusion, the military supports the implementation of government policy in Papua via territorial, intelligence, and combat/ enforcement operations with significant impediments including lack of intelligence, cultural/ linguistic competence, metrics, and a unified command. To improve this, the military needs to provide cultural/ linguistic training, enable point persistent surveillance, stand up a unified structure to coordinate intelligence, and implement viable metrics to assess progress.